The Influence of health students' attitudes on tobacco control and tobacco education on family smoking cessation - Permana, Lies; Ifroh, Riza Hayati; Nurrachmawati, Annisa (Preventia: The Indonesian Journal of Public Health, 2025)
Health students are aware of how smoking affects people's health. They are typically well-equipped to help smokers quit and play a significant role in tobacco control. The purpose of this study was to determine the role that students have in encouraging their families to quit smoking both before and after studying in health faculty, as well as the impact that health students' attitudes and tobacco control education have on these inquiries. In March and April of 2024, a cross-sectional survey was conducted using the GHPSS questionnaire, with 123 student in Universitas Mulawarman, grade 2nd public health faculty. The findings showed that there was a difference in the family’s behavior when it came to encouraging them to quit smoking (p-value 0.0350.05) and tobacco-related education (p-value 0.219>0.05) of their family members in encouraging them to quit smoking. The lack of correlation between these factors suggests that tobacco control-related attitudes and education in educational settings have very little impact on the practice of encouraging families to stop smoking. It is suggested that health student should continue to be given skills training to help smoking cessation.